(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The article discusses the pedagogical aspects of the introduction of multimedia technologies in the preschool education system. Their influence on the formation of professional competencies of future educators is analyzed, and methods for improving the effectiveness of the educational process using modern digital tools are proposed.